Postpartum Depression: Prevention strategies in South East Asia and its possibility of replication in Nepal - Singh, Manisha; Tiwari, Ishwar; Bhandari, Dinesh; Katwal, Basanta (Nepal Journal of Obstetrics and Gynaecology, 2019)
Aims: To identify existing interventions in South East Asian countries implemented to prevent postpartum depression (PPD) and explore the possibility of replication of such interventions in Nepal to reduce it. Methods: The paper reviewed the risk factors and preventive strategies implemented in South East Asian countries to prevent PPD. Results: Enough actions have not been taken to address PPD despite of high prevalence in the reviewed countries (Bangladesh, India, Pakistan, Srilanka and Nepal). However, some of the interventions used such as cognitive behavior therapy, education for girls, poverty alleviation program, participatory approach for empowerment and involvement of community health workers have shown positive impact on reducing PPD. Conclusions: The interventions used in South East Asian countries were simple in design intervention and mostly conducted through community health workers; it showed a possibility of replication in Nepal as it already has sufficient community workforces working in maternal and child health. Keywords: interventions, maternal depression, maternal mental health, post–partum depression, prevention, south asia, strategies